Barbados : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2009)
This report focuses on the observance of standards and codes for the Financial Action Task Force on Money Laundering (FATF-40) recommendations for antimoney laundering (AML) and nine special recommendations on combating the financing of terrorism (CFT) for Barbados. The report discusses recommendations on how the AML/CFT system could be strengthened. It is revealed that law enforcement authorities and the Office of Director of Public Prosecutions are under-resourced in relation to their functions. The competent authorities continue to engage in a wide array of joint law enforcement initiatives.